Update on current evaluation and management of pediatric nasal dermoid. (18th February 2016) - Herrington, Heather; Adil, Eelam; Moritz, Ethan; Robson, Caroline; Perez‐Atayde, Antonio; Proctor, Mark; Rahbar, Reza
Abstract : Objectives/Hypothesis: To review the presentation of congenital pediatric nasal dermoid and present guidelines for its evaluation and management. Study Design: Retrospective chart review from 1970 to 2014 at a tertiary referral children's hospital. Methods: The medical records of all patients diagnosed with a nasal dermoid during the study period were reviewed for demographics, lesion characteristics, imaging, operative details, and outcomes. Results: Ninety‐six patients underwent excision of a congenital nasal dermoid during the study period. The mean age at presentation was 3.1 years (range, 0.1–19.3 years). Thirty‐four (35%) females and 62 (65%) males were included. The most common presentation was a nasal dorsal mass in 66 (69%) patients. Ninety‐two (96%) of the patients underwent preoperative imaging. Seventy‐eight (82%) of the patients did not show any clinical or radiographic evidence of intracranial extension preoperatively. Eighty‐five (89%) of the patients underwent extracranial excision, and 11 (11%) underwent combined intracranial and extracranial excision. Eight patients (8%) presented with recurrence, on average 3.3 years (range, 1–6 years) after initial excision. Mean follow‐up time was 8 years (range, 1–18 years). Conclusion: Preoperative imaging of nasal dermoid is crucial to evaluate for intracranial extension, thus facilitating complete removal. Thin section, high‐resolution magnetic resonance with contrast provides excellent detail of the extent of the nasal dermoid including intracranial extension. Thin‐section high‐resolution computed tomography with multiplanar reformatted images provides complimentary information regarding the bone anatomy of the frontonasal region. Surgical strategy is dictated by preoperative imaging and is dependent on the extent of the lesion, but limited facial incisions are preferred. Level of Evidence: 4. Laryngoscope, 126:2151–2160, 2016